Enhancement of Ta2O5 nanostructures properties via electrochemical anodization synthesis method and surface modification with gold nanoparticles for humidity sensing application / Nur Lili Suraya Ngadiman - Ngadiman, Nur Lili Suraya (2022)
Nanostructured metal oxide have been widely employed in electronic devices as sensing layer. One of the most crucial issue in nanostructure fabrication is to optimize the synthesis method in order to produce high sensitivity and reliable sensor. Due to this issue, a synthesis method with high potential to produce metal oxide nanostructures on tantalum foil substrate, namely anodization, is highlighted in this study and surface modification using doped gold nanoparticles is also implemented to improve the characteristics of the nanostructured sensing layer. A set of parameter has been optimized to synthesis Tantalum Pentoxide (Ta2O5) via anodization synthesis method. Anodization is one of the simplest synthesis methods for fabricating generous nanostructures metal oxide. The purpose of this study is to optimize the anodization time and voltage of Ta2O5, employ the optimized Ta2O5 as humidity sensor and improve the functionality through doping method. The significant growth of anodized Ta2O5 nanotubes has increased the number of pore structures and offered more water absorption active sites for humidity sensing detection. Physical and chemical properties of anodized Ta2O5 nanotubes were justified using FESEM, XRD, EDX, AFM and UVVIS analysis. Synthesizing nanostructures through anodization method producing Ta2O5 nanotubes with pore diameter ranging between 10 to 50 nm. From XRD analysis, cubic crystalline structure was obtained through annealing at 500 °C for 2 hours, thus improved its crystalline structure and generated a favourable medium of interaction.